Deciphering molecular heterogeneity of Indian families with hereditary spherocytosis using targeted next‐generation sequencing: First South Asian study. (10th October 2019) - Aggarwal, Anu; Jamwal, Manu; Sharma, Prashant; Sachdeva, Man Updesh Singh; Bansal, Deepak; Malhotra, Pankaj; Das, Reena
Summary: Defects in various erythrocyte membrane proteins genes (ankyrin, band‐3, β‐ and α‐spectrin and protein 4·2) can cause hereditary spherocytosis (HS). This molecular heterogeneity of HS, together with co‐inherited genetic modifiers, results in marked phenotypic variability among patients. We studied the molecular spectrum and genotype‐phenotype correlations in 73 families (with 113 patients) with HS. Deleterious variants including nonsense (42%), deletions (18%), splice site (20%), missense (10%) and duplication/insertion (10%) were found in 47 patients. The variants detected included sporadic and dominantly‐inherited defects in ANK1 (53·2%), SPTB (36·2%) and SLC4A1 (4·2%) . Compound heterozygous variants in SPTA1 (6·4%) showed autosomal recessive inheritance. Alpha‐spectrin variants were associated with severe anaemia and splenectomy alleviated symptoms. Co‐inherited glucose‐6‐phosphate dehydrogenase (G6PD) deficiency was found in 15%. G6PD variants ( n  = 5) led to greater transfusion requirements (1‐8 times) in males with HS. Homozygosity (41%) for the promoter variant of UGT1A1 (Gilbert syndrome) led to a significantly higher mean bilirubin level (126·54 µmol/l) with a higher frequency of cholelithiasis (30%) ( P  < 0·001). This first‐ever south Asian study on the molecular spectrum of HS found ANK1 and SPTB genes variants to be the commonest with inheritance being sporadic/dominant. Next‐generation sequencing provided a relatively sensitive and rapid tool for molecular diagnosis with a diagnostic yield of 64·4%.